Systematic and objective identification of the microstructure around damage directly from images. (1st March 2016) - de Geus, T.W.J.; Du, C.; Hoefnagels, J.P.M.; Peerlings, R.H.J.; Geers, M.G.D.
Abstract: An original experimental approach is presented to automatically determine the average phase distribution around damage sites in multi-phase materials. An objective measure is found to be the average intensity around damage sites, calculated using many images. This method has the following benefits: no phase identification or manual interventions are required, and statistical fluctuations and measurement noise are effectively averaged. The method is demonstrated for dual-phase steel, revealing subtle unexpected differences in the morphology surrounding damage in strongly and weakly banded microstructures. Graphical abstract: